2016
DOI: 10.1177/230949901602400105
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Condylar Cartilage Thickness and Posterior Condylar Offset of the Femur: A Magnetic Resonance Imaging Study

Abstract: Purpose. To measure the femoral posterior condylar cartilage (PCC) thickness and the posterior condylar offset (PCO) and determine the correlation between the 2 parameters in 530 normal subjects using magnetic resonance imaging (MRI Posterior condylar cartilage thickness and posterior condylar offset of the femur: a magnetic resonance imaging study Conclusion. Femoral PCC thickness was comparable in the medial and lateral sides. Males had thicker PCC in the medial and lateral sides than females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Furthermore, the analysed cohort of Voleti et al-with 100 patients compared to the 517 analysed knee joints in this study-is rather small. The results of Wernecke et al are consistent with our results for PCO, pointing out a significant larger PCO lat in male knee joints and no significant gender dependency of PCO med [28]. Bao et al examined CT scans of 80 patients to investigate posterior FCM [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the analysed cohort of Voleti et al-with 100 patients compared to the 517 analysed knee joints in this study-is rather small. The results of Wernecke et al are consistent with our results for PCO, pointing out a significant larger PCO lat in male knee joints and no significant gender dependency of PCO med [28]. Bao et al examined CT scans of 80 patients to investigate posterior FCM [30].…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with the study of Wernecke et al that analysed MRI scans of 287 male and 243 female patients in order to investigate the morphology of the posterior femoral condyles. Likewise, they found no correlation between patient age and PCO [28]. To the authors' knowledge, there are no other studies examining age-specific differences in FCM in the current literature.…”
Section: Discussionmentioning
confidence: 71%
“…However, there are scant data on the association between gender, knee cartilage defects, and knee morphology. Most anatomical studies that measured femoral PCO had small sample sizes, included no patients with knee joint osteoarthritis, or did not separately analyze the medial and lateral sides [5, 6, 10, 27, 29, 31]. The morphometric characteristics are related to genetic, environmental, and cultural conditions, as well as to lifestyle, health, and functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accurate resection of bone and cartilage to match the thickness of the femoral component restores the posterior femoral joint line. Thus, the posterior condylar cartilage should be considered in deciding the resection depth [31]. A previous study observed that plain radiographs underestimate the size of the femoral condyles compared with MRI [27].…”
Section: Discussionmentioning
confidence: 99%
“…These ranges provide insights into the spread of data points within each specific aspect and offer a clear picture of the diversity and distribution of these measurements. Wernecke et al [ 23 ] used MRI to determine the associations between femoral PCC thickness and PCO in 530 healthy subjects. The authors reviewed the records of 287 male and 243 female patients who underwent MRIs for traumatic soft tissue knee injuries that did not include the femoral PCC and did not have symptomatic knee arthritis.…”
Section: Discussionmentioning
confidence: 99%